Efektivitas Edukasi Berbasis Multimedia terhadap Peningkatan Kepatuhan dalam Pengobatan dan Perawatan Diri pada Pasien Pasca Percutaneous Coronary Intervention (PCI) - Santi Apriyani; Elly Nurachmah; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of multimedia-based education in improving medication adherence and self-care in post-PCI patients. The method used in this study is a literature search based on several online databases such as PubMed, CINAHL, ScienceDirect, Wiley Online, Cambridge Core published from 2017-2021. The results showed that multimedia-based education, including smartphone-based education, text messages, and telephones, effectively increased adherence to medication and self-care in post-PCI patients. In conclusion, the application of multimedia/digital-based interventions and education is a solution that can be applied to inpatient care at home. Keywords: Multimedia-Based Education, Compliance, Post Percutaneous Coronary Intervention